Maintaining the legitimacy of school choice in the segregated schooling environment of Amsterdam. Issue 1 (2nd January 2023) - Sissing, Shelby; Boterman, Willem R.
ABSTRACT: In 2015, Amsterdam implemented a centralised primary school admissions policy, constraining school choice after a long history of highly autonomous schools and free parental choice which has resulted, in part, in the city's segregated schooling environment. Introduced out of concerns of inequality for parents and disorganisation by schools, this policy implemented a uniform choosing procedure and a distance-based priority mechanism. Drawing on interviews with school directors and municipal education officials, this paper examines how schools seek to maintain their legitimacy in a highly segregated school choice environment undergoing constrained change. The Amsterdam case serves as a unique example of local education officials confronting the well-documented negative effects of school choice through policies controlling school choice in an era of global school choice expansion.